Photoresponse, thermal and electrical behaviors of MXene-based polysulfone nanocomposite - Demirelli, Kadir; Barim, Esra; Celik, Aytekin; Yegin, Mustafa; Aksoy, Yunus; Hanay, Oezge; Hasar, Halil (Springer, 2024)
The Ti3C2Tx MXene nanosheet was prepared by 40% (v/v) hydrofluoric acid etching at 20 degrees C for 48 h and delamination of bulk MAX Ti3AlC2 precursor material. A 2D nanomaterial MXene Ti3C2Tx as a nanofiller was introduced to polysulfone (PSulfone) matrix. MXene and PSulfone/MXene nanocomposite systems were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscope, Fourier-transform infrared and thermogravimetric analysis instruments. Dielectric and electrical characterization of PSulfone/MXene nanocomposite was carried out. The electrical resistance of Ti3C2Tx MXene from measurement current (I)-voltage (V) was measured as 116 omega. Pure PSulfone matrix exhibits typical insulator behavior, and MXene exhibits a good conductor behavior. But, when MXene was added to the pure PSulfone matrix, the resistance of the MXene/PSulfone nanocomposite increased moderately compared to that of pure MXene. In spite of the excess of surface functional groups, MXene showed surprisingly good electron transport across the surface, while in the case of PSulfone/MXene nanocomposite, the insulating behavior of PSulfone significantly reduced the electron transport of MXene. The semiconductor behavior of PSulfone/Ti3C2Tx MXene nanocomposite indicates that MXene provides efficient charge carrier transfer in the nanocomposite system. By comparing the TGA results between the PSulfone and different weight ratios of PSulfone/Ti3C2Tx MXene nanocomposites, it was determined that MXene nanosheets had a significant effect in slightly accelerating the thermal degradation of PSulfone. Optical conductivity was investigated by preparing a film of PSulfone/MXene nanocomposite on an interdigital contact. It was observed that the optical current values changed depending on the increasing illumination intensity. Considering current-voltage measurements, the photocurrent generation potential of PSulfone/MXene nanocomposite shows that it can be used in photodevice production.
Keywords: MXene; Polysulfon; Nanocomposite; Dielectric properties; Conductivity; Photoresponse